MODEL OF OCCUPATIONAL HEALTH AND SAFETY MANAGEMENT SYSTEM IN STATIONARY MODE - Матиборський, В. В. (Proceedings of National Aviation University (archive), 2021)
The model of the labor protection management system in the stationary mode is considered taking into account the presence of a person in this system. The model takes into account the presence of man and his mistakes as in the control link and in the managed link. The probability of system failures is analyzed with possible errors in each link.